Jones' Clinical Paediatric Surgery - Hutson, John M.; O'Brien, Michael; Beasley, Spencer W.; King, Sebastian (Hoboken : Wiley, 2014)
Jones' Clinical Paediatric Surgery provides clear-sighted advice on the surgical options available for young patients. Building on the popular and successful style of previous editions, this fully revised seventh edition employs a systematic approach to the childhood diseases that need surgical treatment. It includes more case vignettes and colour photographs, expanded coverage on the use of imaging, and updated approaches to management including laparoscopic operations. Key subject areas are supported by case vignettes in a familiar format similar to what might appear in an OSCE viva. Jones' C.
TreatmentPrognosis; Further reading; Chapter 10 Disorders of Sex Development; Definition; The clinical problems; Practical decisions in management; Further reading; Chapter 11 Anorectal Malformations; Classification; Associated anomalies; Incidence; Clinical features; Imaging; Treatment and prognosis; Further reading; Part III Head and Neck; Chapter 12 The Scalp, Skull and Brain; The infant with a large head; Congenital abnormalities of the cranium; Intracranial tumours; Tumours in the spinal canal; Intracranial vascular disorders; Further reading; Chapter 13 The Eye.
Examination of the child's vision and eye.
Print version record.
Keywords: Children -- Surgery; Child; Infant, Newborn; Surgical Procedures, Operative; Children -- Surgery; Electronic books